2020
DOI: 10.1021/acs.est.0c06569
|View full text |Cite
|
Sign up to set email alerts
|

Effects of In Utero Exposure to Perfluorooctane Sulfonate on Placental Functions

Abstract: Perfluorooctane sulfonate (PFOS) is a metabolic-disrupting chemical. There is a strong association between maternal and cord blood PFOS concentrations, affecting metabolism in early life. However, the underlying effects have not been fully elucidated. In this study, using the maternal−fetal model, we investigated the impact of gestational PFOS exposure on the placental structure and nutrient transport. Pregnant mice were oral gavaged with PFOS (1 or 3 μg PFOS/g body weight) from gestational day (GD) 4.5 until … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 60 publications
(87 reference statements)
0
17
0
Order By: Relevance
“…Placental weight and placenta/fetus weight ratios were increased in treated groups, suggesting compensatory placental growth. Placentas from pregnant mice dosed with PFOS at dosages that caused FGR exhibited a reduction in maternal–fetal transport of glucose and amino acids and increased concentrations of corticosterone (Wan et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Placental weight and placenta/fetus weight ratios were increased in treated groups, suggesting compensatory placental growth. Placentas from pregnant mice dosed with PFOS at dosages that caused FGR exhibited a reduction in maternal–fetal transport of glucose and amino acids and increased concentrations of corticosterone (Wan et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, this is the first report in humans though this phenomenon has been previously observed in animals. 26,27 Li et al found that 20 mg/kg PFOS exposure during pregnancy significantly reduced the BW of Sprague Dawley rat by increasing fetal serum corticosterone levels. 26 Wan et al also reported that pregnant mice exposed to 3 mg/kg PFOS from gestational day 4.5−17.5 reduced the fetal body weight and increased the cortisol levels in the placenta and liver.…”
Section: Influence Of Glucocorticoid On the Association Between Pfas ...mentioning
confidence: 99%
“…26 Wan et al also reported that pregnant mice exposed to 3 mg/kg PFOS from gestational day 4.5−17.5 reduced the fetal body weight and increased the cortisol levels in the placenta and liver. 27 While the underlying mechanism is unknown, more epidemiological and toxicology studies are needed to determine the adverse association between PFAS exposure and fetal growth and the potential mediating role of fetal glucocorticoid.…”
Section: Influence Of Glucocorticoid On the Association Between Pfas ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The placenta is the interface between mother and fetus and is a critical organ modulating fetal development, metabolism, immunity, hormone regulation, and parturition initiation. The transfer of xenobiotics from mother to fetus rarely avoids placental transport, and the placenta is therefore a potential target for fetal exposure to PFASs before birth . Indirect effects via the placenta may account for adverse birth outcomes induced by PFAS prenatal exposure. Despite widespread detection of PFASs in the placenta and toxicological studies reporting PFAS-induced placental injury and dysfunction, ,, no population-based studies on the effects of PFASs on the placenta or the influence of underlying placental injuries on the fetus have been conducted. In addition, for existing studies, the detected placentas were not explicitly analyzed on spatial separation, and the influence of the distinctive structural and functional features of the subchorionic plate (fetal side) and parabasal plate (maternal side) on placental PFAS distribution has been largely ignored. , Accordingly, there is a critical need to investigate region-specific PFAS distribution in the placenta and the corresponding in situ health effects to help elucidate intraplacental distribution and prenatal/perinatal health risks.…”
Section: Introductionmentioning
confidence: 99%